2022
DOI: 10.1101/2022.02.20.22271261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing antibiotic use in Indonesia: a systematic review and synthesis of current evidence to inform opportunities for intervention

Abstract: Introduction A major driver of antimicrobial resistance (AMR) and poor clinical outcomes is suboptimal antibiotic use, although data are lacking in low-resource settings. We reviewed studies on systemic antibiotic use (WHO ATC/DDD category J01) for human health in Indonesia, and synthesized available evidence to identify opportunities for intervention. Methods We systematically searched five international and national databases for eligible peer-reviewed articles, in English and Indonesian, published between … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 106 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…23 The Gyssens method is an instrument that is widely used to evaluate the appropriateness of using antibiotics in the treatment of patients. 22,24,25 The present study showed various causes of irrational use of antibiotics, either as prophylactic or therapeutic. Both the use of other antibiotics should be more efficient, and the inappropriate doses were the main category that often led to irrational assessments of the use of these antibiotics.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…23 The Gyssens method is an instrument that is widely used to evaluate the appropriateness of using antibiotics in the treatment of patients. 22,24,25 The present study showed various causes of irrational use of antibiotics, either as prophylactic or therapeutic. Both the use of other antibiotics should be more efficient, and the inappropriate doses were the main category that often led to irrational assessments of the use of these antibiotics.…”
Section: Discussionmentioning
confidence: 61%
“…11 Based on a systematic review, it was also stated that those included in the top 15 antibiotics most commonly consumed in Indonesia are β-lactams, especially cephalosporin and penicillins. 22 Bacterial culture was not usually performed on digestive surgery patients. The therapeutic antibiotic used in the present study was empirical antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…It is predicted that NDP will continue to increase. NDP is a challenge in the world of health (Limato et al, 2022).…”
Section: Ndp (Non-communicable Diseases) Programmentioning
confidence: 99%